Effects of amphibian skin secretion molecules on rabies virus infection in mammalian cells - Vigerelli, H.; Sciani, J. M.; Jared, C.; Antoniazzi, M. M.; Caporale, G. M. M.; Silva, A. C. R.; Pimenta, D. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Texto em inglês